Analisis Jaringan Aktor: Upaya Pemerintah Mendorong Masyarakat Belanja Produk UMKM Lokal : (Studi pada Kantor Pelayanan Pajak Cirebon Satu) - Utomo, Rachmad; Slamet, Kuwat; Sulfan, Sulfan; Theodikta, Mohammed Lintang; Dhaniswara, Angga Sukma (Jurnal Ilmiah Administrasi Publik, 2023)
This study aims to describe the experience of the stages of translation in actor network theory: (1) problematization, (2) interessment, (3) enrollment and (4) mobilization that have been carried out by the Cirebon Satu Tax Service Office in realizing an online shopping day for SME products (Harbolkum) in the city of Cirebon. This study uses a narrative qualitative approach to explore the social experience of a single character or main actor, the Head of the Cirebon Tax Office. The results of this study indicate that at the stage of (1) problematization, the main actor it is special person to be able to formulate the main issues that only possible implemented and also the results are useful with the supporting actors (2) interessment, optimizing strategies to attract and encourage the interest of supporting actors, (3) enrolment, the role of delegation without any disturbing between authority and (4) mobilization, the main actors together with the coalition invite elite figures in built solid frame to reach a broad impact on mobilization.